Tool path generation on doubly-curved free-form surfaces. Issue 6 (19th September 2017) - Halbritter, J.; Harik, Ramy; Zuloaga, A.; vanTooren, M.
ABSTRACT: In the industries of automobiles and aerospace, the use of carbon fiber has grown exponentially over the years due to its high specific mechanical properties. However, the existing processes for the placement of these fibers within these industries remain either restrictive to the doubly-curved free-formed surfaces required or economically unfeasible in respect to the larger scaled components desired. This paper presents a tool path generation process which will produce non-collisional pathing for the automated placement of uniform fibers on scalable doubly-curved free-formed surfaces. To begin this process, a high detail model of the component part is given and analyzed for optimizing the placement of both the part and the KUKA robot. We account for variable fiber placement angles based on design specifications of the part. The process will begin with a given three-dimensional rendering of the component model which will be transformed into a readable Robotic Scripting Language (RSL) file that the machine will be able to understand. This research is intended for the eventual development of manufacturing support software for automated fiber placement (AFP). GRAPHICAL ABSTRACT: